Precocious Torpor in an Altricial Mammal and the Functional Implications of Heterothermy During Development - Geiser, Fritz; Wen, Jing; Sukhchuluun, Gansukh; Chi, Qing-Sheng; Wang, De-Hua (Frontiers in Physiology, 2019)
Most mammals and birds are altricial, small and naked at birth/hatching. They attain endothermic thermoregulation at a fraction of their adult size at a vulnerable stage with high heat loss when many could profit from using torpor for energy conservation. Nevertheless, detailed data on the interrelations between torpor expression and development of endothermic thermoregulation are currently restricted to <0.1% of extant endotherms. We investigated at what age and body mass (BM) desert hamsters (Phodopus roborovskii), wild-caught in Inner Mongolia and born in autumn/early winter when environmental temperatures in the wild begin to decrease, are able to defend their body temperature (Tb) at an ambient temperature (Ta) of ~21°C and how soon thereafter they could express torpor. Measurements of surface temperatures via infrared thermometer and thermal camera show that although neonate hamsters (BM 0.9±0.1 g) cooled rapidly to near Ta, already on day 15 (BM 5.5±0.2 g) they could defend a high and constant Tb. As soon as day 16 (BM 5.8±0.2 g), when their maximum activity metabolism (measured as oxygen consumption) approached maxima measured in vertebrates, animals were able to enter torpor for several hours with a reduction of metabolism by >90%, followed by endothermic arousal. Over the next weeks, torpor depth and duration decreased together with a reduction in resting metabolic rate at Ta 30-32°C. Our data show that development of endothermy and torpor expression in this altricial hamster is extremely fast. The results suggest that precocious torpor by juvenile hamsters in autumn and winter is an important survival tool in their vast and harsh Asian desert habitats, but likely also for many other small mammals and birds worldwide.